The effect of differences in the management of mild pain with and without hypnotherapy speakers in post-operative cancer patients - Sugiyono, Iis; Suardi, Achmad; Suryani, Suryani; Anwar, Anita Deborah; Rowawi, Roni; Wijayanegara, Hidayat (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background: Cancer, a prevalent non-communicable disease globally and in Indonesia, poses significant health challenges. Pain, a frequent and dreaded symptom in cancer patients, can severely impact their functional abilities, quality of life, and elevate stress levels within families. Non-pharmacological approaches to pain management, like hypnotherapy, offer safe, affordable, and readily applicable solutions.Objectives: This research seeks to evaluate the impact of varying approaches to managing mild pain, specifically comparing the use of hypnotherapy speakers versus their absence, in post-operative cancer patients at RSPAD Gatot Soebroto during the period from December 2023 to January 2024.Methods: This quantitative study employs a Quasi-Experimental design with a Two Group Pretest-Posttest format. The research took place in the Obstetrics Ward on the second floor of PIS RSPAD Gatot Soebroto from December 16, 2023, to January 17, 2024. A total of 44 participants were included, divided into a control group and an intervention group. Data collection was carried out using observation sheets and universal pain assessment tools. Descriptive statistics were analyzed using univariate analysis, and normality tests were performed before conducting bivariate analysis to assess data distribution.Results: The research revealed a notable decrease in pain scores following the use of hypnotherapy speakers. Initially, the average pain score was 2.59 (SD=0.59) prior to the therapy, which dropped to 0.73 (SD=0.83) post-therapy. Both the administration of Paracetamol alone and in combination with hypnotherapy speakers significantly alleviated pain in patients with ovarian and cervical cancer (p<0.001). Moreover, a significant difference was observed between the intervention and control groups in the post-test results (p=0.004).Conclusions: These results suggest that combining Paracetamol with hypnotherapy speakers is more effective at alleviating pain in patients with ovarian and cervical cancer than using Paracetamol alone. This study serves as a valuable reference for future research on the utilization of hypnotherapy speakers and offers practical guidance for midwives to adopt hypnotherapy speakers to expedite pain relief in cancer patients.